HOSPITAL - DOCTORS' ABILITY TO INTERPRET ECGS - Khattak, M Tahir (Journal of Ayub Medical College Abbottabad, 1992)
ABSTRACT The electrocardiogram is an important part of the patient's clinical assessment. A correct interpretation of the ECG is essential for a proper evaluation, as important management decisions may need to be taken based on the ECG findings. This study was carried out to assess the ability of hospital-doctors' to interpret ECG's reflecting common clinical conditions. Overall senior physicians performed better than their junior colleagues. Efforts need to be made to train the junior doctors in electrocardiography as they are at the fore-front in dealing with acute cardiac and medical emergencies.